WAQF AS AN INSTRUMENT FOR YOUTH EMPOWERMENT TO ATTAIN THE HIGH LEVEL OF HUMAN CAPITAL FOR PEACEFUL COEXISTENCE IN KANO - Gwadabe Nura Abubakar; Asmak Ab Rahman (Journal of Islamic, Social, Economics and Development, 2021)
The Study was aimed in examining the Potentials of Waqf for youth empowerment for attaining high level of Human capital among the Youth for peaceful coexistence in Kano state Nigeria. Human Capital signifies the Knowledge, attitude, expertise and skills possess by Human being, It is believe that Human capital is the most significant factor among the factors of production, it direct the other factors of production in the provision of good and services to the nation towards the attainment of social and economic development. Awqaf institutions have played a vital role to the development of Human capital in various Muslim Communities more specifically through Education, Hygiene and Health Care Services. The Studies has shown that Nigeria was ranked the 11th in the world among the countries that has the highest labor force, and most of these youth are either unemployed or unemployable. These youth can be easily recruited into thuggery, political violence and other social vices that will disturb the peace and peaceful coexistence of the state. To ensure peace and security in Kano, utmost priority must be given to Youth Empowerment in the areas of Education, training, skills and abilities of the youth. The study adopted the qualitative method of research, whereas, relevant documents were consulted as structured interview was designed to ascertain the role of waqf based youth empowerment programs in achieving high level of human capital in Kano. The data were analyzed using thematic data analysis. The study concluded that Awqaf institutions in Kano has played a vital role in the Youth empowerment for the actualization of High level of Human capital in Kano towards the attainment of peaceful society.